The Role of Employee Engagement in Mediating Perceived Organizational Support and Job Satisfaction on Employee Performance at PT Krakatau Bandar Samudera - Aramiko Kayanie Nenden Atryana; Tata Rustandi; Udin Suadma (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee performance is the key to success for a company. However, in this phenomenon, there are several reasons why employee performance has not reached the target expected by the company. This study aims to analyze the role of employee engagement that mediates perceived organizational support and job satisfaction on employee performance at PT Krakatau Bandar Samudera. This study adopted a quantitative method with a population of 442 employees of PT Krakatau Bandar Samudera, and 82 employees as samples using proportional random sampling techniques. This data was collected through a questionnaire using a Likert scale and analyzed using Smart PLS 4.10. The results of the study from the measurement of t-statistics of the relationship between variables in this model structure showed that perceived organizational support had a negative effect of -46.25, while job satisfaction had a positive and significant impact on employee performance of 4.606. In addition, perceived organizational support had a positive and significant impact on employee engagement of 1.708. However, there was no effect of perceived organizational support on employee performance through employee engagement of 2.743.